GAYA KEPEMIMPINAN KHARISMATIK KEPALA MAD RASAH ALIYAH DALAM MENINGKATKAN KOMPETENSI KEPRIBADIAN GURU DI PONDOK PESANTREN MODERN DARUL HIKMAH KECAMATAN SIRANDORUNG - Yuni Yuni; T. Darmansah; Mesiono Mesiono (Hijri, 2023)
The research that has been carried out is entitled "The Charismatic Leadership Style of the Aliyah Madrasah Head in Increasing Teacher Personality Competence at Darul Hikmah Sirandorung Modern Islamic Boarding School". The purpose of this study was to find out: (1) How is the leadership style of the modern madrasah aliyah principal Darul Hikmah Sirandorung, (2) How the teacher's personality competence in the modern aliyah Islamic boarding school is Darul Hikmah Sirandorung, (3) how the head of madrasah aliyah's efforts are in improving the teacher's personality competence at the modern Islamic boarding school Darul Hikmah Sirandorung. In this thesis research, the researcher uses a qualitative approach. While the data collection techniques were carried out by means of: observation, interviews and documentation. Data analysis techniques used in this study are: data reduction, data presentasion and drawing conclusions. Meanwhile, in the technique of checking the validity of the data, it is done by testing the level of trust (credibility), transferability (transferability), dependence (dependability), and certainty (confirmability). The results of the study revealed that: (1) the charismatic leadership style of the madrasah aliyah principal is to always prioritize the self-authority of a leader who is shown by a high sense of responsibility to his subordinates. (2) the personality competencies of teachers in modern Islamic boarding schools Darul Wisdom Sirandorung are quite good and some teachers have mastered the indicators of teacher personality competencies in accordance with government regulations. (3) the efforts of the head of madrasah aliyah in improving the competence of the teacher's personality by participating in education and training through supervision, panel discussions, workshops, and seminars. This growth is expected to support teachers in fulfilling their duties and responsibilities as professional educators who have good personality competencies.Keywords: Charismatic  Leadership  Style,  Head  of  Madrasah,  TeacherPersonality Competence